Stunting Prevention Program (Zero New Stunting) for Pregnant and Breastfeeding Women in Tanjungjaya Village, Barjarwangi, Garut - Adiansyah, Adi; Suhendi, Fika Dita; Rukmana, Alvi; Subhan, Subhan; Rohmatunisa, Putri Rahayu; Salsabila, Nabil; Hapsyah, Ayu Siti; Widaningsih, Fitri; Rohmah, Sasqia; Rahmawati, Eli Rahmawati; Rohman, Aria Fatur; Khoirunnurfauzan, M. Raka Alfansyah (Fakultas Kewirausahaan Universitas Garut, 2025)
Stunting has more than just physical growth implications; it has long-term effects on cognitive development, productivity, and health in adulthood, and is one of the factors hindering the development of a nation's human resources. The high prevalence of stunting in Indonesia makes prevention and treatment efforts very important. This Community Health Program (PKM) aims to educate the community of Tanjungjaya Village, particularly pregnant women and breastfeeding mothers, about the prevention and management of stunting, as well as the dangers associated with it. The implementation of this PKM involves a socialization campaign that includes education on the prevention and management of stunting, as well as the distribution and planting of moringa trees over a one-month period, located at 11 Posyandu centers in Tanjungjaya Village.